Analysis of the Application of Unlawful Act Elements in Corruption Crime Cases against North Sulawesi Bank Debtors (Review of Decision Number 11/Pid.Sus-TPK/2021/PN Gto) - Uloli, Frengki; Nur, Rafika; Arti, Asdar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was conducted to determine the extent to which material criminal law was applied in the panel of judges' consideration of elements of unlawful acts in cases of criminal acts of corruption where the defendant was a debtor who had defaulted (bad credit) on his loan installments. Knowing the extent to which judges provide legal considerations using the lex specialist derogate generaly principle approach, as well as the existence of contradictions between Constitutional Court Decision Number 003/PUU-IV/2006 in the criminal justice practice order. The results of this research show that judges still apply unlawfulness in a positive function first without conducting an in-depth study and truly exploring whether the act is indeed an act that is considered evil and reprehensible to the wider community. Judges, in looking at the unlawful nature of material law, must consider the unlawful nature of the law in its negative function, not only in its positive function, so that actions carried out, even though they meet the formulation of an offense but do not violate negative material law, can be used as a justification that does not harm the state, does not benefit themselves, other people and corporations and the perpetrator's legal obligations are not subject to punishment.